The role of immunohistochemical analysis in determining the molecular subtypes of bladder cancer - M. V. Berkut; A. S. Artemyeva; A. V. Khokhlova; A. I. Saad; A. K. Nosov (Успехи молекулярной онкологии, 2024)
Introduction. The results of genomic profiling of muscle-invasive bladder cancer (BC) based on messenger RNA (mRNA) extraction showed significant molecular variety of the tumors underlying the wide spectrum of clinical manifestations and responses to traditional treatment methods. However, despite the valuableness of molecular mRNA profiling for understanding biological behavior of the tumor, its implementation in routine clinical practice is complicated due to technological complexity and high cost of genomic sequencing. Therefore, determination of BC molecular subtype based on immunohistochemical examination can be considered an alternative to mRNA profiling. However, the method should be validated using clinical material.Aim. To evaluate prognostic significance of immunohistochemical method in determination of urothelial cancer molecular subtype using a surrogate panel consisting of 13 markers and semiquantitative calculation of the histochemical index.Materials and methods. The retrospective cohort study included 49 patients with BC who underwent radical cystectomy (RC) after previous transurethral resection (TURBT) between 2013 and 2016 at the center. The inclusion criteria were patient age between 18 and 75 years, histologically verified BC, and availability of formalin-fixed paraffin embedded blocks after TURBT and RC at the Clinical Laboratory of Morphology. The exclusion criteria were rare histological types of BC, grade IV–V surgical complications per the Clavien–Dindo classification during hospitalization, TURBT performed at other medical facilities. Molecular subtypes were determined using the immunohistochemical method on the Ventana BenchMark XT (Roche, USA) immunostainer per the traditional technique for deparaffinized sections with subtype-specific panel consisting of 13 antibodies recommended by the Lund taxonomy (LundTax). Depending on the hyperexpression level of basal and/or luminal antibodies, 4 urothelial cancer subtypes were identified: luminal А (UroA), luminal В (UroB), basal and genomically unstable (GU). The first endpoint of the study was 5-year recurrence-free survival on TURBT and RC material, secondary endpoint was 5-year overall survival on the same material.Results. Using immunohistochemical analysis with a surrogate marker panel of preserved histological material after TURBT, urothelial cancer subtype was determined in 38 (77.6 %) patients, after RC – in 39 (79.5 %) patients. Percentages of UroA, UroB and GU subtypes after TURBT and RC were almost identical; the rarest type was Basal with 4 (8.2 %) and 5 (10.2 %) cases, respectively. Evaluation of the primary endpoint showed that 5-year recurrence-free survival after TURBT (log-rank test; p = 0.85) and RC (log-rank test; p = 0.95) did not differ in various urothelial cancer subtypes. Evaluation of the secondary endpoint did not show significant statistical difference in 5-year OS1 (log-rank test; p = 0.94) and OS2 (log-rank test; p = 0.92). Multivariate regression analysis showed that the most significant predictors of BC recurrence after radical treatment were clinical stage IIIA (p = 0.017) and pathomorphological stage II (p = 0.021), while OS rates were significantly affected by pathomorphological stages IIIA (p = 0.003) and IVA (p = 0.019).Conclusion. Determination of urothelial cancer molecular subtype using a surrogate panel of 13 markers and semiquantitative calculation of the histochemical index did not show effectiveness and prognostic significance: the identified 4 subtypes of urothelial cancer did not significantly affect long-term oncological outcomes.